Strategi Kerjasama Pedagang di Pasar Tradisional Pakong Pamekasan dalam Meningkatkan Pendapatan - Muayyad, Ubaidullah; Alief Rifky, Nuzulul; Maksum (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
Abstract Cooperation between merchants has actually been going on for a long time but it runs naturally. We can see things that naturally happen, namely cooperation in terms of helping to promote, assisting in terms of funding and the like that we can find in people's markets. In the Pakong Pamekasan market, such a condition has occurred, a condition where the cooperation of traders has carried out natural cooperation, some of which are through contracts, some are also due to the existence of associations that encourage such cooperation. Therefore, researchers are interested in conducting research in traditional markets in the district. Pakong kab. Pamekasan aims to find out and analyze whether the cooperation carried out by traders can increase income. This research is a field research using a qualitative approach. To get the data, the writer uses the media of interview, observation and documentation.The result of this research is that the cooperation carried out by traders in the Pakong market is dominated by a cooperation system based on mutual assistance and mutual assistance, namely spontaneous cooperation, such as combining capital, taking goods or stocking up. goods first and then pay later according to the agreement, and also help each other promote, this is intended to increase sales intensity and increase revenue. One of the factors that influence the income of traders in the Pakong market is the cooperation system. Cooperation more or less has a very significant impact on most traders. Cooperation helps with systems and agreements that are mutually beneficial for both parties. The agreement is the key to the cooperation system, how in the agreement no one is harmed. Keywords: Cooperation, Merchant, Income Increase